Reading, writing, and rigor : helping students achieve greater depth of knowledge in literacy - Boyles, Nancy N., 1948- (ASCD, 2018)
"Tackles the essence of what teachers need to know about how Depth of Knowledge and its associated rigors are measured on standards-based assessments. Specifically, readers learn how each DOK rigor aligns with standards, text complexity, close reading, student interaction, the reading-writing connection, and formative assessment"--